Neisseria meningitidis Translation Elongation Factor P and Its Active-Site Arginine Residue Are Essential for Cell Viability. - Tatsuo Yanagisawa; Hideyuki Takahashi; Takehiro Suzuki; Akiko Masuda; Naoshi Dohmae; Shigeyuki Yokoyama (PLoS ONE, 2016)
Translation elongation factor P (EF-P), a ubiquitous protein over the entire range of bacterial species, rescues ribosomal stalling at consecutive prolines in proteins. In Escherichia coli and Salmonella enterica, the post-translational β-lysyl modification of Lys34 of EF-P is important for the EF-P activity. The β-lysyl EF-P modification pathway is conserved among only 26-28% of bacteria. Recently, it was found that the Shewanella oneidensis and Pseudomonas aeruginosa EF-P proteins, containing an Arg residue at position 32, are modified with rhamnose, which is a novel post-translational modification. In these bacteria, EF-P and its Arg modification are both dispensable for cell viability, similar to the E. coli and S. enterica EF-P proteins and their Lys34 modification. However, in the present study, we found that EF-P and Arg32 are essential for the viability of the human pathogen, Neisseria meningitidis. We therefore analyzed the modification of Arg32 in the N. meningitidis EF-P protein, and identified the same rhamnosyl modification as in the S. oneidensis and P. aeruginosa EF-P proteins. N. meningitidis also has the orthologue of the rhamnosyl modification enzyme (EarP) from S. oneidensis and P. aeruginosa. Therefore, EarP should be a promising target for antibacterial drug development specifically against N. meningitidis. The pair of genes encoding N. meningitidis EF-P and EarP suppressed the slow-growth phenotype of the EF-P-deficient mutant of E. coli, indicating that the activity of N. meningitidis rhamnosyl-EF-P for rescuing the stalled ribosomes at proline stretches is similar to that of E. coli β-lysyl-EF-P. The possible reasons for the unique requirement of rhamnosyl-EF-P for N. meningitidis cells are that more proline stretch-containing proteins are essential and/or the basal ribosomal activity to synthesize proline stretch-containing proteins in the absence of EF-P is lower in this bacterium than in others.